Amino acid-based multiresponsive low-molecular weight metallohydrogels with load-bearing and rapid self-healing abilities - Saha, Subhadeep; Bachl, Jurgen; Kundu, Tanay; Diaz, David Diaz; Banerjee, Rahul (Chemical Communications, 2014)
A multiresponsive metallohydrogel based on an amino acid-derived low molecular weight (LMW) ligand and a Zn(II) salt was prepared. This hydrogel showed remarkable shape-persistent, self-standing, load-bearing and self-healing properties, which is uncommon in LMW hydrogels.